Reviewing the legal enforcement in the usage authorisation of pesticides in agricultural industries in Malaysia / Hatin Nabihah Mohamad Zamri … [et al.] - Mohamad Zamri, Hatin Nabihah; Jasmi, Akmar Naqhi; Mohd. Idris, Martina; Zulkifli, Nur Dura Munirah (2013)
The study is carried out to review the legal enforcement in the usage authorisation of pesticides in agricultural industries in Malaysia. The research will be based on qualitative type of research by focusing on data gathered from various written sources as well as interviews conducted with legal experts. It will focus on the legal enforcement regarding the unauthorised usage of pesticides in the agricultural industries especially in the paddy industries in Malaysia which are ineffective and inadequate. The provision governing the pesticides law in Malaysia in found lacking and incomprehensive. The current law does not adequately act as a guideline to authorise the usage of pesticides in the agriculture industry in Malaysia. Thus, the research done has some recommendation proposed at the end of this research in view of improving the Act and thereby provides a more comprehensive guideline. Later it will instil awareness towards the user of the pesticides in the paddy industry in regards of safe use of pesticides.